PERSPEKTIF EKONOMI ISLAM TERHADAP PENETAPAN NISBAH BAGI HASIL TABUNGAN UMUM SYARIAH DI BMT UGT NUSANTARA CAPEM NUSA DUA KEDONGANAN BADUNG BALI - Hasan, Zainol; Syarifuddin, Syarifuddin; Lutfiyah, Sri (Al-Idarah, 2023)
Since the time of Rasulullah SAW, the economy of Muslims has been carried out with contracts that are in accordance with sharia and have become a tradition. Islamic economics is a social science that studies the economic problems of society based on Islamic values. The instrument used to apply sharia principles in the financial sector is the Baitul Maal wat Tamwil (BMT). One of them is BMT UGT Nusantara Sub Branch Nusa Dua. In sharia savings at BMT UGT Nusantara Sub Branch Nusa Dua, the percentages are set from BMT, but the process for taking profit sharing ratios is not explained, so it is not known whether the profit sharing has been fair or not. Based on this phenomenon, the focus of research is how to determine the profit sharing ratio for sharia savings at BMT UGT Nusantara Sub Branch Nusa Dua? and what is the review from the perspective of Islamic economics?. In this study, researchers used a type of qualitative research. Data collection are observation, interview and documentation. There are three procedures in data analysis techniques, they are: data reduction, data presentation and data verification. Determination of profit-sharing ratios for sharia savings using a akad musyarakah with a profit sharing of 70% for BMT and 30% for members. The nominal amount of profit-sharing rupiah for each member will differ depending on the length and amount of money kept at the BMT. The Islamic economic perspective on determining profit sharing ratios through musyarakah contracts in BMT is in accordance with Islamic economic principles because it has been fair.